Assessing What Matters Most in Health Insurance Choices: An IPMA Study of Customer Attitude and Perceived Credibility As Mediators - Banerjee, Rathindranath; S, Anjani Devi; Giribabu , Palisetti (International Journal of Accounting and Economics Studies, 2025)
This study investigates the influence of perceived value, digital platform quality, and trust on purchase intention toward health insurance, emphasizing the mediating roles of customer attitude and perceived credibility. Drawing from the Theory of Planned Behavior and service quality literature, this research adopts a quantitative approach, collecting data from 421 policyholders across South India using a structured questionnaire. Structural Equation Modeling (PLS-SEM) was employed to examine the hypothesized relationships, followed by Importance-Performance Map Analysis (IPMA) to prioritize managerial actions. The results reveal that trust and perceived value significantly impact purchase intention, both directly and indirectly through the mediators. Digital platform quality influences purchase intention mainly through enhanced perceived credibility and positive attitudes. IPMA findings further suggest that while trust and customer attitude are of high importance, their performance remains suboptimal, indicating a gap that insurers need to address. The study provides valuable insights for policymakers and insurance companies aiming to enhance consumer engagement by focusing on improving digital experience, transparency, and overall perceived value. Practical implications and strategic recommendations are discussed for creating more customer-centric insurance services.
Keywords: Digital platform quality, Perceived value, Trust, Attitude, Health insurance, IPMA